Decreased plasma tryptophan concentration in major depression: relationship to melancholia and weight loss. - Anderson, I; Parry-Billings, M; Newsholme, E; Poortmans, JR; Cowen, P (1990)
Plasma total tryptophan (TRP) concentration was significantly lower in 31 patients with major depression compared to a healthy control group. The ratio of plasma TRP concentration to that of other branch chain amino acids (the TRP:BCAA ratio) was also decreased. Further analysis revealed that the decrease in plasma TRP and TRP:BCAA ratio was most apparent in patients with major depression and melancholia. Overall, women but not men had significantly decreased plasma tryptophan concentrations, perhaps because of a contributory effect of weight loss; this latter effect, however, could not be distinguished clearly from a diagnosis of melancholia. Our data suggest that in some depressed patients, reductions in plasma tryptophan availability may contribute to abnormalities in brain 5-hydroxytryptamine function.